2014
DOI: 10.15740/has/ijpp/7.2/339-344
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different insecticides against sucking pests in brinjal

Abstract: An experiment was conducted to study the bio-efficacy of nine different insecticides (triazophos 0.08 %, imidacloprid 0.002 %, profenophos 0.05 %, diafenthiuron 0.05 %, clothianidin 0.025 %, cartap hydrochloride 0.05 %, thiamethoxam 0.025 %, thiacloprid 0.012 % and spiromesifen 0.024 %) again sucking pests viz., jassid and whitefly in brinjal (GBH 1) at Main Vegetable Research Station, Anand Agricultural University, Anand during Rabi season of 2011-12. Among different insecticides evaluated, thiamethoxam, diaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Razaq et al (2005) found that diafenthiuron gave high mortality of jassid and whitefly. The present observations also corroborated with those of Shaikh et al (2012) on spiromesifen and diafenthiuron against whitefly and diafenthiuron against jassid. Reddy et al (2014) reported >80% mortality A. craccivora in cowpea with dimethoate (0.06%).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Razaq et al (2005) found that diafenthiuron gave high mortality of jassid and whitefly. The present observations also corroborated with those of Shaikh et al (2012) on spiromesifen and diafenthiuron against whitefly and diafenthiuron against jassid. Reddy et al (2014) reported >80% mortality A. craccivora in cowpea with dimethoate (0.06%).…”
Section: Resultssupporting
confidence: 90%
“…and emamectin benzoate (27.47); and the least was 4.80 obtained withNSKE, azadirachtin (9.34) and B. bassiana (9.87). These results are partially in agreement with those ofShaikh et al (2012) on diafenthiuron;Anandmurthy et al (2017) observed maximum grain yield of cowpea 853 kg/ ha with dinotefuran followed by acetamiprid, spiromesifen and dimethoate. On the benefit cost ratio, acetamiprid (21.8) proved to be most economically viable followed by dimethoate (21.2) Choudhary et al (2017).…”
supporting
confidence: 89%
“…Thiamethoxam: Foliar application of thiamethoxam @100 g/ha was found significantly effective over control which recorded 1.25 whiteflies/leaf followed by seed treatment with thiamethoxam 500 FS @ 4.0 ml/kg seed in soybean (AICRP report on Soybean, 2005-06). Shah et al (2007) reported that thiamethoxam 25 WS @ 0.005 % was highly effective by recording lowest population of 2.60 whiteflies per plant and also recorded lowest MYMV incidence (10.7 %) in greengram. Verma and Kanwar (2009) reported that the lowest leafhopper population (0.84/ plant) was observed in seed treatment with thiamethoxam 70 WS @ 3 g /kg seed (0.84/plant) at 20 DAS in green gram.…”
Section: Organophosphates and Synthetic Pyrethroidsmentioning
confidence: 97%
“…Bioefficacy of newer insecticide molecules against Tea Mosquito Bug revealed that among all the treatments, Tolfenpyrad 15% EC treated tea shoots at 72 HAT had 100 percent adult mortality followed by Dinotefuran 20% SG (100.00%), Sulfaxaflor 21. The spray application of imidacloprid, thiamethoxam, and diafenthiuron effectively reduced the sucking pests population on chilli, brinjal and arecanut were reported by [1,16,17] and [18]. According to Venkateshalu and Mahesh [19], dinotefuran 20 % SG @ 30 g a.i./ha was found highly effective against sucking pests of Okra.…”
Section: Resultsmentioning
confidence: 99%